Methodology for the analysis of dietary data from the Mexican National Health and Nutrition Survey 2006 Metodología para el análisis de información dietética de la Encuesta Nacional de Salud y Nutrición 2006 - Sonia Rodríguez-Ramírez; Verónica Mundo-Rosas; Alejandra Jiménez-Aguilar; Teresa Shamah-Levy (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To describe the methodology for the analysis of dietary data from the Mexican National Health and Nutrition Survey 2006 (ENSANUT 2006) carried out in Mexico. MATERIAL AND METHODS: Dietary data from the population who participated in the ENSANUT 2006 were collected through a 7-day food-frequency questionnaire. Energy and nutrient intake of each food consumed and adequacy percentage by day were also estimated. Intakes and adequacy percentages > 5 SDs from the energy and nutrient general distribution and observations with energy adequacy percentages < 25% were excluded from the analysis. RESULTS: Valid dietary data were obtained from 3552 children aged 1 to 4 years, 8716 children aged 5 to 11 years, 8442 adolescents, 15951 adults, and 3357 older adults. CONCLUSIONS: It is important to detail the methodology for the analysis of dietary data to standardize data cleaning criteria and to be able to compare the results of different studies. OBJETIVO: Describir la metodología de análisis de la información dietética de la Encuesta Nacional de Salud y Nutrición de México (ENSANUT 2006). MATERIAL Y MÉTODOS: Se recolectó de la ENSANUT 2006 información dietética de la población mediante un cuestionario de frecuencia de consumo de siete días. Se estimó la ingesta y porcentaje de adecuación de energía y nutrimentos. Se excluyeron del análisis porcentajes de adecuación > 5 DE de la distribución general de energía y nutrimentos y observaciones con porcentaje de energía <25%. RESULTADOS: Se obtuvo información dietética válida de 3552 niños de entre 1 a 4 años de edad, 8716 niños de 5 a 11 años de edad, 8442 adolescentes, 15 951 adultos y 3357 adultos mayores. CONCLUSIONES: Detallar la metodología de análisis de la información dietética sirve para estandarizar los criterios de limpieza de la información y hacer comparables los resultados entre diferentes estudios.